2018
DOI: 10.21855/ecociencia.52.60
|View full text |Cite
|
Sign up to set email alerts
|

cultura organizacional: Abordaje conceptual y delimitación de variables para su estudio.

Abstract: En la actualidad las organizaciones se enfrentan a constantes retos en correspondencia con las expectativas del mundo globalizado. Esto lleva al desarrollo de las organizaciones y las relaciones laborales, siendo el personal la clave del éxito por encontrarse detrás de todo proceso de gestión. Al valorarar los intangibles relacionados con las buenas prácticas en la gestión del talento humano, la situación se vuelve compleja, puesto que las variables que las componen (cultura; clima; calidad de vida laboral), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Considering these elements, Chiavenato (2009) and Schein (2010) establish a direct relationship between the importance of communication and the adverse effects it can cause, aligned with the findings where it is observed that the participants manifest symptoms of demotivation and frustration, and even the participants themselves relate it to the tense atmosphere within the team, a situation that ends up leading to staff turnover. Similarly happens with the policies and processes of benefits and rewards, identifying that both for the participants and Llanos and Bell (2018), it is a crucial…”
Section: ) Communication and Interaction Between Different Hierarchic...mentioning
confidence: 99%
See 2 more Smart Citations
“…Considering these elements, Chiavenato (2009) and Schein (2010) establish a direct relationship between the importance of communication and the adverse effects it can cause, aligned with the findings where it is observed that the participants manifest symptoms of demotivation and frustration, and even the participants themselves relate it to the tense atmosphere within the team, a situation that ends up leading to staff turnover. Similarly happens with the policies and processes of benefits and rewards, identifying that both for the participants and Llanos and Bell (2018), it is a crucial…”
Section: ) Communication and Interaction Between Different Hierarchic...mentioning
confidence: 99%
“…Highlevel managers could even impose them as a rule defined by them. This scenario could develop a micro-management environment throughout the whole organization, making micro-management a mandatory practice and organizational convention, used not only by high and old organizational levels but also by new resources and lower organizational levels to adapt themselves under this alignment (Llanos & Bell, 2018). However, even though the literature mentioned delves into the topic of micro-management in the field of business management, there are no studies on micromanagement in the specific area of project management, so in the academy and good industry practices, relevant studies are not observed, that establish the relationship between micro-business management and its presence in project management, which accommodates empirical research that can develop this theme, as is this case.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation